(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the issues of improving the methodology of training future teachers to form a healthy lifestyle in students. In the context of globalization and digital development, the introduction of information and communication technologies into the educational process is considered an important factor in developing a culture of healthy living. As part of the study, based on a questionnaire conducted among 91 students, their attitude to a healthy lifestyle, methodological readiness, and skills in using modern pedagogical technologies were studied. The results showed that the majority of respondents consider themselves ready in this area, but some students lack practical and methodological experience. Based on the data obtained, increasing practical training, organizing training and seminars, using digital resources, and strengthening interdisciplinary integration were identified as priority areas for improving the methodology. The results of the study confirm the need to develop an innovative approach and theory-practice integration in preparing future educators to promote a healthy lifestyle.